Home country advantage? The influence of Italian, German and Austrian employee representatives in the UniCredit European Works Council. (June 2016) - Cavallini, Michela; Gold, Michael; Royle, Tony; Senatori, Iacopo
This article examines the first European Works Council (EWC) to be established in the Italian banking sector, at UniCredit. It focuses on the interaction between Italian, German and Austrian delegations of employee representatives and on the perspectives and practices that reflect their different cultural and institutional backgrounds in industrial relations. Much of the literature suggests that employee representatives from the home country of a multinational company are likely to mould EWC structures in accordance with their own national backgrounds and have greater confidence in dealing with central management in EWC meetings. Our findings partly substantiate this argument, but also suggest that minority delegations, when they have the benefit of strong national institutional arrangements and less fragmented union patterns, are more likely to be cohesive and experienced and therefore are able to challenge management and sometimes win significant arguments over strategy.